Desempeño laboral de las secretarias y su relación con la calidad en la atención a los estudiantes de la Facultad de Ciencias Jurídicas, Sociales y de la Educación de la Universidad Técnica de Babahoyo - Arreaga Castro, Lady Gissela (2018)
The economic and social success of a company depends in part on the entities it has. Through their good performance in quality management ensure that the company is competitive. It is the executive assistants who project the image of their company to the public and the work environment. It is considered that among the most important characteristics that a secretary should have to collaborate positively in the institution is the adaptation to the way of working of their boss and have dynamism and ability to communicate, in the same way this must have the full confidence of delegating in she part of the work she develops, she must know how to provide effective support in achieving the objectives and results. Their role is to support management, so they are not only limited to transactional tasks, but must be directly involved in all the activities of their immediate superior and the team they report to. They must also provide ideas and solutions to situations and often serve as interlocutors between the superior and the other members of the organization. In the development of the present investigation, the type of exploratory, descriptive and explanatory research, documentary and field modality was applied, applying observation cards, surveys and interviews, which gave results that were later analyzed and interpreted to conclude and recommend the proposal that is set out below: Program to improve the skills of the secretaries in terms of their functions and attention to students and users.